Group signatures from lattices : simpler, tighter, shorter, ring-based - Ling, San (2015)
We introduce a lattice-based group signature scheme that provides several noticeable improvements over the contemporary ones: simpler construction, weaker hardness assumptions, and shorter sizes of keys and signatures. Moreover, our scheme can be transformed into the ring setting, resulting in a scheme based on ideal lattices, in which the public key and signature both have bit-size e õ(n ∙ logN), for security parameter n, and for group of N users. Towards our goal, we construct a new lattice-based cryptographic tool: a statistical zero-knowledge argument of knowledge of a valid message-signature pair for Boyen's signature scheme (Boyen, PKC'10), which potentially can be used as the building block to design various privacy-enhancing cryptographic constructions.